Income inequality and the German export surplus - Ansgar Rannenberg; Thomas Theobald (National Bank of Belgium, 2022)
We investigate the contribution of the increase in German (DE) income inequality to the German export surplus increase and the decline of the natural rate of interest in the Euro Area in an open economy model with rich and non-rich households. Rich households have Capitalist Spirit type Preferences (CSP) over their wealth and thus save out of an increase in their permanent income. Simulating the increase in DE income inequality over the 1992-2016 period generates a decline of the EA natural rate of interest rate of about 1 p.p. and an increase of the DE net-export-to-GDP ratio of about 3 p.p..
Keywords: 330; Einkommensverteilung; Export; Handelsbilanz; Zins; Deutschland; Eurozone